PEMANFAATAN ARSIP RESEP DALAM ANALISIS TINGKAT KEPATUHAN DOKTER PADA PENULISAN RESEP PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM KOTA MATARAM - Muhammad Aditya Rachman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2026)
Prescription records are an essential form of dynamic archives in healthcare institutions that support administrative accountability and clinical decision-making. This study aims to analyze physicians’ compliance in prescription writing based on prescription archive data of outpatients at Mataram City General Hospital. The research used a descriptive quantitative method with a cross-sectional approach supported by archival document analysis. A total of 200 prescription records were analyzed using completeness indicators based on pharmaceutical service standards. The results showed that the level of physician compliance reached 78%, categorized as fairly good. However, several components such as dosage, physician signature, and patient identity were still incomplete. From an archival perspective, properly managed prescription records enable systematic, accurate, and accountable evaluation of healthcare services. This study highlights the importance of strengthening archival management systems to improve data quality and patient safety.